2003
DOI: 10.1155/2003/907042
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Inelastic Scattering as a High‐Resolution Vibrational Spectroscopy: New Tool for the Study of Protein Dynamics

Abstract: We have applied inelastic neutron scattering (INS) to the understanding of protein dynamics. INS spectrum of staphylococcal nuclease (SNase) at 25 K in the energy range between 100 and 4000 cm −1 is compared with the result of normal mode calculation. The theoretical spectrum is in general agreement with experiment and is used to assign the peaks. INS spectra show some significant differences for the folded and the unfolded SNase. The intensity distribution of INS spectrum is different from protein to protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As described in ref , TOSCA has revealed itself to give detailed results combined to optical spectroscopic techniques such as Raman spectroscopy due to its design associating a single momentum transfer with each energy transfer. Furthermore TOSCA has been successfully used for investigating biological systems, such as globular proteins, collagen and model polypeptides , and interfacial water. , …”
Section: Methodsmentioning
confidence: 99%
“…As described in ref , TOSCA has revealed itself to give detailed results combined to optical spectroscopic techniques such as Raman spectroscopy due to its design associating a single momentum transfer with each energy transfer. Furthermore TOSCA has been successfully used for investigating biological systems, such as globular proteins, collagen and model polypeptides , and interfacial water. , …”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the INS technique is particularly useful in the studies on the deformation modes in which the vibrations of hydrogen atoms are involved [24][25][26]. This is due to the large incoherent scattering cross-section of hydrogen and the high amplitudes of these vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy by inelastic neutron scattering (INS) has, in principle, a natural utility for the investigation of biological systems because of the large sensitivity of neutrons to H in incoherent scattering. Globular proteins [15][16][17][18], collagen and model polypeptides [19,3] and hydration water [4,20] have all been studied with the use of INS, as also have been the structures of interfacial water associated with DNA and gelatin molecules [2]. Only rather qualitative inferences could be drawn from these spectra, namely that at low hydration levels the spectral contribution of hydration water differs strongly from the spectrum of the ice Ih and may be viewed as being more similar to HDA ice, while at high hydration levels the spectrum has a more ice-like appearance.…”
Section: Introductionmentioning
confidence: 99%